The Contagion Effect of Low-Quality Audits at the Level of Individual Auditors - Li, Liuchuang; Qi, Baolei; Tian, Gaoliang; Zhang, Guochang (The Accounting Review, 2017)
ABSTRACT This study examines the relation between the audit failures of individual auditors and the quality of other audits performed by these same auditors. Employing a Chinese setting where audit reports reveal the identities of engagement auditors, we find that auditors who have performed failed audits also deliver lower-quality audits on other audit engagements, with this “contagion” effect spreading both over time and to other audits performed by these same auditors in the same year. However, we find little evidence that an audit failure also casts doubt on the quality of audits performed by “non-failed” auditors who are same-office colleagues of a “failed” auditor. We further discover that the contagion effect is attenuated for female auditors, auditors holding a master's degree, and auditors with more auditing experience. Our results underscore the usefulness of disclosing the identity and personal characteristics of individual auditors to investors and regulators.